2020
DOI: 10.5194/amt-13-5725-2020
|View full text |Cite
|
Sign up to set email alerts
|

Application of time-of-flight aerosol mass spectrometry for the real-time measurement of particle-phase organic peroxides: an online redox derivatization–aerosol mass spectrometer (ORD-AMS)

Abstract: Abstract. Aerosol mass spectrometers (AMS) are frequently applied in atmospheric aerosol research in connection with climate, environmental or health-related projects. This is also true for the measurement of the organic fraction of particulate matter, still the least understood group of components contributing to atmospheric aerosols. While quantification of the organic and/or inorganic aerosol fractions is feasible, more detailed information about individual organic compounds or compound classes can usually … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…To address this issue, several online techniques have been developed. A good example is the adoption of the offline TPP method 471 in the AMS-TPP method, 216 but this method can only measure total PO without further speciation. Furthermore, molecular-level character-ization of POs is needed to complement nonspecific bulkphase assays in order to understand PO chemistry and impacts.…”
Section: Detection Of Posmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, several online techniques have been developed. A good example is the adoption of the offline TPP method 471 in the AMS-TPP method, 216 but this method can only measure total PO without further speciation. Furthermore, molecular-level character-ization of POs is needed to complement nonspecific bulkphase assays in order to understand PO chemistry and impacts.…”
Section: Detection Of Posmentioning
confidence: 99%
“…TPP can rapidly react with peroxides to form spectroscopically detectable triphenylphosphine oxide (TPPO) (Figure S3). Recently, this method was coupled with an aerosol mass spectrometer (AMS) for real-time quantification of bulk POs in SOA, which is less sensitive to interferences such as molecular oxygen compared to the conventional UV–vis-based iodometry method due to the slower reaction rate between TPP and oxygen . The 4-nitrophenylboronic acid (4-NPBA) assay was also developed to quantify the bulk POs (Figure S4), where organic hydroperoxides are reactive toward 4-NPBA and form a yellow product (4-nitrophenol) that exhibits significant light absorption at 406 nm. , …”
Section: Recent Developments In Analytical Techniques For Po Detectionmentioning
confidence: 99%
“…Given the ubiquity and lability of organic peroxides and their essential role in the formation, aging, and health impacts of aerosols, efforts have been made to understand their particle-phase reactivity in recent decades. , , ,, However, the chemical lability and complexity of organic peroxides and the lack of appropriate standards pose a big challenge to the molecular identification and quantification of these compounds. , As a result, most studies have focused on the characterization of bulk organic peroxides in SOA, , ,,, normally with spectrophotometric methods, such as iodometry/UV–visible spectrophotometry, , or a combination of derivatization methods and spectrometry. , It has been shown that the bulk organic peroxides in SOA (e.g., from monoterpene oxidation) generally decay on timescales of hours to days at room temperature due to particle-phase reactions such as thermolysis, hydrolysis, or photolysis, , while the most reactive fraction of organic peroxides in SOA, such as HOMs, decay with an average half-lifetime of tens of minutes at room temperature …”
Section: Introductionmentioning
confidence: 99%
“…44,45 As a result, most studies have focused on the characterization of bulk organic peroxides in SOA, [15][16][17][18][26][27][28]36,37,40 normally with spectrophotometric methods, such as iodometry/UV−visible spectrophotometry, 12,21 or a combination of derivatization methods and spectrometry. 46,47 It has been shown that the bulk organic peroxides in SOA (e.g., from monoterpene oxidation) generally decay on timescales of hours to days at room temperature due to particle-phase reactions such as thermolysis, hydrolysis, or photolysis, [15][16][17]40 while the most reactive fraction of organic peroxides in SOA, such as HOMs, decay with an average half-lifetime of tens of minutes at room temperature. 18 The development of mass spectrometry (MS) enables characterization of specific organic compounds in SOA.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous investigations in aqueous-phase OH-radical-initiated oxidation of varying water-soluble organic precursors, there is a lack of laboratory evidence which can assist in deconvoluting varying reaction pathways and the conditions favorable to the formation of peroxides. Detection of organic peroxides and their radical intermediates can be challenging due to (i) lack of selective analytical technique to allow targeted analysis, (ii) lability due to weak O–O bond, , (iii) inaccessibility of sensitive radical measurement techniques (e.g., EPR) to capture crucial RO 2 intermediates formed during autoxidation, making it difficult to determine the underlying mechanism pertaining to their formation, and (iv) incorporation of unrealistic experimental conditions including UV light and oxidant/precursor concentrations during fundamental laboratory investigations. In particular, unambiguous identification of organic peroxides using direct mass spectrometric (MS) measurements can be difficult due to the inability of MS to provide functional group information and successive fragmentations of molecules in the ion molecular region. , As such, chemically derivatized methods can be useful for the successful characterization of select functional groups. Based on the work of Zhao et al, a combination of MS with the chemical assay of iodometry has proven to be advantageous for the selective identification of organic peroxides in a complex matrix …”
Section: Introductionmentioning
confidence: 99%